Bridge deck assessment using infrastructure corrosion assessment magnetic method (iCAMM™) technology, a case study of a culvert in Markham city, Ontario, Canada. (December 2020) - Mosharafi, M.; Mahbaz, S.B.; Dusseault, M.B.
Abstract: Steel reinforcement corrosion can result in disastrous bridge failures over time. To manage the human and financial risks associated with such unexpected functional bridge failures, the reinforcements' condition should be quantified using Non-Destructive Testing (NDT) methods. In this case history, the condition of culvert C072's reinforced concrete (RC) bridge structure (located in the north of Markham, Ontario, Canada) is inspected. The inspection, carried out under the supervision of the Corporation of the City of Markham, used a passive magnetic-based NDT technology, the Infrastructure Corrosion Assessment Magnetic Method (iCAMM™). The inspection outcomes demonstrate that the sections close to the south and north ends of the bridge display the most-severe reinforcement anomalies: roughly, a maximum of 20% and 14% of the reinforcement's cross-sectional area loss are detected close to the bridging structure's south and north ends. Additionally, an area in the middle of the bridge is found to have a noticeable anomaly in the reinforcement. The results generated from the magnetic data, collected using an iCAMM™ scanner, are in good agreement with visual-investigation results and the culvert's historical information, such as the concrete's chloride content and compressive strength values, as well as information from a half-cell potential survey. Culvert C072's condition is considered moderately deteriorated and corrective actions are recommended. Highlights: The condition of a culvert's reinforced concrete (RC) is inspected. The inspection is carried out using a passive magnetic-based NDT technology. Inspection results obtain an overview of the culvert's corrosion conditions. Results agree with historical information on the culvert.